Pengaruh model pembelajaran make a match dan minat belajar terhadap keterampilan menulis pantun kelas v sd negeri se-kecamatan ngadirojo - Manunggal, Mugi Siti; Slamet, Slamet (Universitas Sebelas Maret, 2025)
This research aims to determine: 1) differences in pantun writing skills between students who are taught using the learning model Make A Match and learning model Think Pair Share (TPS), 2) differences in pantun writing skills between students who have high learning interest and low learning interest, 3) whether or not there is an interaction between the learning model and learning interest on students' pantun writing skills. This research uses a quantitative approach with experimental methods and a 2x2 factorial research design. The research population consisted of all fifth grade students at State Elementary Schools in Ngadirojo District. Sample selection uses techniques cluster random sampling. Data collection techniques include tests and questionnaires. Data analysis used two-way ANOVA. The results of the research show that: 1) There are differences in pantun writing skills of students who are taught using the learning model Make A Match with students who are taught using a learning model Think Pair Share (TPS), because FA = 5,60 > Ftable = 4.08, 2) There is a difference in pantun writing skills of students who have high learning interest and students who have low learning interest, because FB = 144,6 > Ftable = 4.08, 3) There is an interaction between the learning model and learning interest towards pantun writing skills, because FAB = 14,26 > Ftable = 4,08.